GIS Applications for Water, Wastewater, and Stormwater Systems - Shamsi, U.M. (CRC Press, 2009)
Professionals involved in the planning, design, operation, and construction of water, wastewater, and stormwater systems need to understand the productivity-enhancing applications of GIS. Inspired by an ASCE-sponsored continuing education course taught by the author, GIS Applications for Water, Wastewater, and Stormwater Systems focuses on the practical aspects of software and data tools that enable GIS applications. The book documents and analyzes effective use of GIS, demonstrating how you can apply the technology to make tasks easier to perform, saving time and money for your organization.